Immune checkpoint inhibitors in cervical cancer: Current status and research progress - Xie, Yunkai; Kong, Weimin; Zhao, Xiaoling; Zhang, He; Luo, Dan; Chen, Shuning (Frontiers in Oncology, 2022)
Cervical cancer is the second most common gynecological malignant tumor endangering the health of women worldwide. Despite advances in the therapeutic strategies available to treat cervical cancer, the long-term prognosis of patients with recurrent and metastatic cervical cancer remains unsatisfactory. In recent years, immune checkpoint inhibitors (ICIs) have shown encouraging efficacy in the treatment of cervical cancer. ICIs have been approved for use in both first- and second-line cervical cancer therapies. This review summarizes the current knowledge of ICIs and the application of ICIs in clinical trials for the treatment of cervical cancer.